OPTIMIZATION OF COMBUSTION CONTROL IN INDUSTRIAL FURNACES - Ibragimov Islomnur; Ibragimov Begobod Sheraliyevich (Galaxy International Interdisciplinary Research Journal, 2023)
The control of combustion processes largely determines the efficiency of the fuel facility, and hence the environmental pollution caused by it. An optimization of the control of combustion processes in industrial plants is proposed, covering the static regime of almost inertial chemical transformations and the dynamic regime of inertial heat transfer in the combustion chamber.